Too many cooks - Bate, Dana (Kensington Books, 2015)
When Kelly Madigan is offered a job abroad right after reading a letter from her late mother urging her to take more risks, she sees it as a sign. Kelly's new ghostwriting assignment means moving to London to work for Natasha Spencer--movie star, lifestyle guru, and wife of a promising English politician. As it turns out, Natasha is also selfish, mercurial, and unwilling to let any actual food past her perfect lips. Still, in between testing dozens of kale burgers and developing the perfect chocolate mousse, Kelly is having adventures. Some are glamorous; others, like her attraction to her boss's neglected husband, are veering out of control. Kelly knows there's no foolproof recipe for a happy life. But how will she know if she's gone too far in reaching for what she wants?